Hermeneutic Of Pesantren With The " Fusion Of Horizons " Gadamer’s Theory - Taufikin Taufikin (Southeast Asian Journal of Islamic Education, 2018)
Islamic boarding schools (Pesantren) are an Islamic educational institution that has been established for a long time before Indonesia's independence, the existence of pesantren has been tested despite the conditions that are often not impartial. This simple paper aims to examine the early history of the emergence of pesantren to date with a focus on the forms. The hermeneutical approach of Hans Georg Gadamer's "Fusion of Horizons" theory is used to analyze more about the pesantren from its ince ption until present . The result of this study is that pesantren were initially established because of a cleric and santri who were interacting in learning, to be able to make it Islamic boarding school ( huts , dormitories , surau, dayah, rangkang, and meruasa). As the santri rise, the kyai lifts the teacher (ustadz) to help him. Then the pesantren self-characterized in accordance with the results of understanding and interpretation of the kyai adapted to the context, so that now ap pears the pesantren Qur'an, pesantren salaf and modern pesantren. The alternative researcher " a contemporary boarding school " that is not only based on salaf, Qur'an, Science and Technology, but also makes santri the solution provider towards every pattern of life.